Case-ascertainment of acute myocardial infarction hospitalisations across two national data sources for an English cardio-oncology cohort. (14th October 2021) - Coles, B; Teece, L; Adlam, D; Sweeting, M J; ,
Abstract: Background: Cardio-oncology is an emerging field aimed at minimising cardiovascular morbidity and mortality in survivors of cancer. Though cardio-oncology patients make up a significant proportion of hospital admissions, they are typically excluded from clinical trials. Electronic health record-based research is a good alternative to understand the risk of cardiovascular disease in these patients. However, completeness and validity of cardiovascular outcome ascertainment may vary by data source. Purpose: 1) Determine ascertainment of acute myocardial infarction (AMI) hospitalisations across two national data sources for English cancer patients, and 2) understand factors that affect ascertainment in this population. Methods: English cancer patients were obtained from the National Cancer Registration and Analysis Service. AMI hospital admissions occurring during 2010–2017 were identified from two sources: the Myocardial Ischaemia National Audit Project (MINAP) registry and Hospital Episode Statistics (HES). Admissions were ascertainable from both MINAP and HES, or "matched", if dated within 30 days. Results: 112, 502 hospital admissions for 95, 509 patients were identified of which 57, 265 (50.9%) admissions were captured in MINAP and HES, 26, 104 (23.2%) in MINAP only, and 29, 133 (25.9%) in HES only. Case-ascertainment percentages were similar across cancer site, stage and grade of disease. Cases ascertained from MINAP only were younger, had fewer comorbidities, and were more likely to have ST-elevated MI and better survival than those ascertained from HES only. The percentage of admissions that could be ascertained from both MINAP and HES has improved from over time. Conclusions: MINAP and HES define different populations of cancer patients with AMI. Only half of AMI hospital admissions were captured in both MINAP and hospital records. Therefore, these results support the use of multiple linked data sources for observational cardio-oncological research into AMI. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation and Cancer Research UK